SUV-quantification of physiological lung tissue in an integrated PET/MR-system: Impact of lung density and bone tissue. - Ferdinand Seith; Holger Schmidt; Sergios Gatidis; Ilja Bezrukov; Christina Schraml; Christina Pfannenberg; Christian la Fougère; Konstantin Nikolaou; Nina Schwenzer (PLoS ONE, 2017)
The aim of the study was to investigate the influence of lung density changes as well as bone proximity on the attenuation correction of lung standardized uptake values (SUVs).15 patients with mostly oncologic diseases were examined in 18F-FDG-PET/CT and subsequently in a fully integrated PET/MR scanner. From each PET dataset acquired in PET/MR, four different PET reconstructions were computed using different attenuation maps (μ-maps): i) CT-based μ-map (gold standard); ii) CT-based μ-map in which the linear attenuation coefficients (LAC) of the lung tissue was replaced by the lung LAC from the MR-based segmentation method; iii) based on reconstruction ii), the LAC of bone structures was additionally replaced with the LAC from the MR-based segmentation method; iv) the vendor-provided MR-based μ-map (segmentation-based method). Those steps were performed using MATLAB. CT Hounsfield units (HU) and SUVmean was acquired in different levels and regions of the lung. Relative differences between the differently corrected PETs were computed.Compared to the gold standard, reconstruction ii), iii) and iv) led to a relative underestimation of SUV in the posterior regions of -9.0%, -13.4% and -14.0%, respectively. Anterior and middle regions were less affected with an overestimation of about 6-8% in reconstructions ii)-iv).It could be shown that both, differences in lung density and the vicinity of bone tissue in the μ-map may have an influence on SUV, mostly affecting the posterior lung regions.